2015
DOI: 10.3892/etm.2015.2208
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility and osteogenic properties of porous tantalum

Abstract: Porous tantalum has been reported to be a promising material for use in bone tissue engineering. In the present study, the biocompatibility and osteogenic properties of porous tantalum were studied in vitro and in vivo. The morphology of porous tantalum was observed using scanning electron microscopy (SEM). Osteoblasts were cultured with porous tantalum, and cell morphology, adhesion and proliferation were investigated using optical microscopy and SEM. In addition, porous tantalum rods were implanted in rabbit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 22 publications
3
54
0
1
Order By: Relevance
“…Wang et al prepared porous tantalum by the powder metallurgy technique and implanted into the femoral condyle of rabbits. 40 But this method is difficult to get high open-cell porous metals. In recent years, with the rapid development of 3D printing technology, net-shape porous tantalum has been created with laser engineered net shaping technique and applied for bone defects in rat.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al prepared porous tantalum by the powder metallurgy technique and implanted into the femoral condyle of rabbits. 40 But this method is difficult to get high open-cell porous metals. In recent years, with the rapid development of 3D printing technology, net-shape porous tantalum has been created with laser engineered net shaping technique and applied for bone defects in rat.…”
Section: Discussionmentioning
confidence: 99%
“… Histological observation of hard tissue in contact with porous tantalum implants at week ( A ) 2; ( B ) 4; ( C ) 8 and ( D ) 12 after implantation (methylene blue staining). Reproduced with permission from [ 95 ]. …”
Section: Figurementioning
confidence: 99%
“…7,8 Porous Ta, also called porous Ta trabecular metal (PTTM), contains a co-adjacent vesicular framework that is similar to cancellous bone with pore sizes ranging from 300 to 600 μm and a porosity of 75%-85%, and its elastic modulus (1.3-10 GPa) is similar to that of natural cortical (12-18 GPa) and cancellous bone (0.1-0.5 GPa). 9 Porous Ta is non-toxic, highly corrosion resistant, biocompatible, and bioactive; 10 it allows both bone ingrowth and ongrowth and promotes osteogenesis to establish osseointegration and osseoincorporation, thus significantly enhancing the initial stability of implants 9,11 and the applicability to osteo-regenerative strategies. 12 Currently, porous Ta has been widely applied in orthopedic applications and oral implants, and studies have shown that it can highly promote the adhesion, proliferation, differentiation, and mineralization of osteoblasts in vitro 3,13,14 and in vivo.…”
Section: Introductionmentioning
confidence: 99%